Comparison of cell‐loading methods in hydrogel systems. Issue 4 (22nd May 2013) - Ma, Jinling; Yang, Fang; Both, Sanne K.; Kersten‐Niessen, Monique; Bongio, Matilde; Pan, Juli; Cui, Fu‐Zhai; Kasper, F. Kurtis; Mikos, Antonios G.; Jansen, John A.; van den Beucken, Jeroen J. J. P.
Abstract: Bone regenerative medicine, based on the combined use of cells and scaffolds, represents a promising strategy in bone regeneration. Hydrogels have attracted huge interests for application as a scaffold for minimally invasive surgery. Collagen and oligo(poly(ethylene glycol)fumarate) (OPF) hydrogels are the representatives of two main categories of hydrogels, that is, natural‐ and synthetic‐based hydrogels. With these the optimal cell‐loading (i.e., cell distribution inside the hydrogels) method was assessed. The cell behavior of both bone marrow‐ and adipose tissue‐derived mesenchymal stem cells (BM‐ and AT‐MSCs) in three loading methods, which are dispersed (i.e., homogeneous cell encapsulation, D), sandwich (i.e., cells located in between two hydrogel layers, S), and spheroid (i.e., cell pellets encapsulation, Sp) loading in two hydrogel systems (i.e., collagen and OPF), was compared. The results suggested that the cell behavior was influenced by the hydrogel type, meaning cells cultured in collagen hydrogels had higher proliferation and osteogenic differentiation capacity than in OPF hydrogels. In addition, AT‐MSCs exhibited higher proliferation and osteogenic properties compared to BM‐MSCs. However, no difference was observed for mineralization among the three loading methods, which did not approve the hypothesis that S and Sp loading would increase osteogenic capacity compared to D loading. In conclusion, D and Sp loading represents two promising cell loading methods for injectable bone substitute materials that allow application of minimally invasive surgery for cell‐based regenerative treatment. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 935–946, 2014.